The development of a biological pretreatment strategy for the conversion of wheat straw to biofuels or platform chemicals - Pensupa, Nattha (2015)
The increasing concern of energy shortage and environmental pollution attracts worldwide exploration of using sustainable biomaterials for the production of biofuels and biochemicals. Utilising lignocellulosic raw materials for valuable bio-products production is generally considered as a preferred biosynthetic technology. Although various processes have already been proposed, lignocellulose hydrolysis is still remaining as one of the major challenges that prevents wide spread application of lignocellulosic raw materials in biofuel and biochemical production. The aim of this study was to investigate the feasibility of applying soft-rot fungi as a biological pretreatment of wheat straw for the generation of cellulase enzymes and then use the freshly produced enzymes to hydrolyse the fermented wheat straw to a sugar rich hydrolysate. The wheat straw hydrolysate had also been examined for the production of bioethanol and biochemicals, such as succinic acid and itaconic acid. Solid State Fermentations (SSF) of wheat straw were carried out using both Aspergillus niger and Trichoderma reesei. The fermentation conditions, such as moistures content, culture time, addition of nutrients, and modification of wheat straw were optimised for the production of cellulase. In a SSF using autoclaved wheat straw, an enzyme activity of 9.5 FPU/g was achieved. When 0.5% yeast extract and mineral solution were added, the enzyme activities increased to 24.0 FPU/g after 5 days of cultivation. In a SSF of an alkali soaked wheat straw (wheat straw treated with 1% NaOH at 25˚C for 24 hours), 21.8 FPU/g was obtained after just 1-day culture. Optimisation of hydrolysis process led to a hydrolysate containing 59.8 g/L glucose, which was achieved from the hydrolysis of biologically pretreated wheat straw at 18% solid loading, with an enzyme loading rate of 55 FPU/g at 50˚C. Fermentations using the wheat straw hydrolysate resulted in 28.6 g/L ethanol, which was equivalent to 93.4% of theoretic yield. Utilisation of wheat straw hydrolysate for succinic acid production was investigated using recombinant yeast strains. For Saccharomyces cerevisiae D2, the deletion of SDH1 and SDH2 genes enhanced succinic acid production by 68%. Optimisation of fermentation conditions and fermentation scales led to a succinic acid production to around 12 g/L, which was nearly 100-folds of what succinic acid production using the wild S. cerevisiae D2 strain at initial fermentation conditions. Use wheat straw hydrolysate to replace commercial glucose based semi-defined medium resulted in the same succinic acid production yield, but lower concentration due to the low sugar concentration in the hydrolysate. Biosynthesis of itaconic acid using wheat straw hydrolysate was also explored, but no significant itaconic acid production was observed.